Alih Fungsi Lahan dan Curah Hujan terhadap Perubahan Hidrologi Sub Das Samin - Nining Rahayu; Sutarno Sutarno; Komariah Komariah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2017)
Samin sub-watershed is located in the district of Karanganyar and Sukoharjo regency. Every year an increasing number of people in Samin sub-watershed can inflict problems such as the seizure of land use and the amount of available water resources. This study purpose to analyzed the influence of land conversion and rainfall to hydrology conditions Samin sub-watershed in 2005-2015. This research used descriptive exploration method. The study population was the whole unit of land use in the Samin sub-watershed. Data collection techniques used collection of secondary data from BPS Karanganyar-Sukoharjo regency and watering hall. Data were analyzed using correlation analysis of land use and rainfall on hydrology conditions Samin sub-watershed. The results showed that the wetland and forest land decreased by an average of 44,76 ha-1year and 102,5 ha-1year. Residential land, fields and plantations increased by an average of 26,8ha-1year, 54,07ha-1year and 26,82ha-1year. In period 2005-2010 and 2011-2015, Samin sub-watershed has declined average on annual charge (-3.117,42 m3/second), value of coefficient run-off (-0,11), sedimentation (-0,01 mm) and increase average on value of coefficient of river regime (+91,02) and CVcharge (+0,35). Results of statistical analysis of correlation showed that, decline in wetland, forest and increased fields affect the increase coefficient of river regime. Decreased forest land also increased of fields land and plantations affect the increase of Coefficients of Variants (CVcharge). Decreased forest land affects decreased run-off coefficient, sedimentation and annual discharge.